2022
DOI: 10.1007/s11033-022-07257-9
|View full text |Cite
|
Sign up to set email alerts
|

Splice-disrupt genomic variants in prostate cancer

Abstract: Background Splice-disrupt genomic variants are one of the causes of cancer-causing errors in gene expression. Little is known about splice-disrupt genomic variants. Methods and results Here, pattern of splice-disrupt variants was investigated using 21,842,764 genomic variants in different types of prostate cancer. A particular attention was paid to genomic locations of splice-disrupt variants on target genes. HLA-A in prostate cancer, MSR1 in familial pros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…Only one study so far has profiled the different splice-disrupt genomic variants in CaP and reported HLA-A in primary CaP, MSR1 in familial CaP, and EGFR in both CRPC and metastatic CRPC with the highest allele frequencies of splice-disrupt variations [ 133 ]. Nonetheless, several splice-disrupting genomic variants have been predicted during different stages of CaP progression, which impact cancer-relevant genes such as EGFR [ 133 ]. The extent to which these predictions hold true is yet to be fully determined.…”
Section: Molecular Basis For Shifts In Alternative Splicing Patterns ...mentioning
confidence: 99%
“…Only one study so far has profiled the different splice-disrupt genomic variants in CaP and reported HLA-A in primary CaP, MSR1 in familial CaP, and EGFR in both CRPC and metastatic CRPC with the highest allele frequencies of splice-disrupt variations [ 133 ]. Nonetheless, several splice-disrupting genomic variants have been predicted during different stages of CaP progression, which impact cancer-relevant genes such as EGFR [ 133 ]. The extent to which these predictions hold true is yet to be fully determined.…”
Section: Molecular Basis For Shifts In Alternative Splicing Patterns ...mentioning
confidence: 99%